2017
DOI: 10.1371/journal.pone.0176016
|View full text |Cite
|
Sign up to set email alerts
|

Muscle contributions to medial tibiofemoral compartment contact loading following ACL reconstruction using semitendinosus and gracilis tendon grafts

Abstract: BackgroundThe muscle-tendon properties of the semitendinosus (ST) and gracilis (GR) are substantially altered following tendon harvest for the purpose of anterior cruciate ligament reconstruction (ACLR). This study adopted a musculoskeletal modelling approach to determine how the changes to the ST and GR muscle-tendon properties alter their contribution to medial compartment contact loading within the tibiofemoral joint in post ACLR patients, and the extent to which other muscles compensate under the same exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 44 publications
0
28
0
1
Order By: Relevance
“…In that study, it was shown that simpler knee models can produce similar cartilage responses with more complex models. The FE model with motion implemented using kinetics and kinematics (forces and rotations), and without patella and quadriceps forces, produced reaction forces and contact pressures within physiological limits (Gilbert et al, 2014;Konrath et al, 2017;Kutzner et al, 2010;Pizzolato et al, 2017). Details of the material properties for each soft tissue are shown in Table 1.…”
Section: Fe Model Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, it was shown that simpler knee models can produce similar cartilage responses with more complex models. The FE model with motion implemented using kinetics and kinematics (forces and rotations), and without patella and quadriceps forces, produced reaction forces and contact pressures within physiological limits (Gilbert et al, 2014;Konrath et al, 2017;Kutzner et al, 2010;Pizzolato et al, 2017). Details of the material properties for each soft tissue are shown in Table 1.…”
Section: Fe Model Constructionmentioning
confidence: 99%
“…Postoperatively, knee OA can be present even in short-term follow-ups of ACLR (Culvenor et al, 2015;Eckstein et al, 2015;Williams et al, 2017). One of the mechanisms leading to OA for ACLR patients could be altered joint biomechanics and excessive stresses and strains experienced by articular cartilage (Gardinier et al, 2013;Konrath et al, 2017;Wellsandt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…At many locations autografts represent the gold standard of ligament reconstruction, associated with limited availability and donor site morbidity. 40 Therefore, biological tissue engineered constructs would be appreciated as a novel approach. So far no tissue engineering-based ligament reconstruction strategy is available for clinical application.…”
Section: 25-28mentioning
confidence: 99%
“…This previous work, however, has generally ignored another critical aspect of muscle actions: how muscles act on internal joint structures such as ligaments or articular cartilage between bones 11 . Although muscle actions on internal joint structures have been considered in clinical biomechanics or sports medicine in the context of injuries [12][13][14][15] , their more general role in the context of the neural control of movement and how they are balanced with task goals remains poorly understood. We examine these issues in this study, evaluating the hypothesis that the nervous system chooses muscle activations to achieve task performance while minimizing internal joint stresses and strains.…”
Section: Introductionmentioning
confidence: 99%